Characteristics of first sexual intercourse among secondary school students in Slovenia - Švab, Alenka (Teorija in praksa, 2021)
The article presents data on the social characteristics of first sexual intercourse (FSI) among secondary school students in Slovenia, collected as part of the research project 'Sexuality of Secondary School Students in Slovenia'. The results show that for most respondents their FSI was a planned event occurring within an intimate partnership. Protective measures are used to a considerable extent. There are statistically significant gender differences in the majority of the results. The data show responsible behaviour during the FSI, although a share of the respondents is exposed to sexually transmitted infections (STIs). The data may be used for policy decision-makers, especially in terms of sex education and addressing the STI issue.
Keywords: Dijaki; High school students; nosečnost; prvi spolni odnos; Sexual intercourse; Spolno občevanje; spolno prenosljive okužbe; starost